2023
DOI: 10.1007/s00264-023-05719-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infections after stabilization of pelvic ring injuries: a retrospective analysis of risk factors and a meta-analysis of similar studies

Abstract: Purpose Pelvic ring fractures requiring surgical stabilization are severe injuries. Surgical site infections occurring after stabilization of the pelvis are serious complications, requiring complex and multidisciplinary treatment. Methods This is a retrospective observational study from a level I trauma centre. One hundred and ninety-two patients who underwent stabilization of closed pelvic ring injuries without signs of pathological fracture were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Tsugawa et al reported that E. coli and Bacteroides are the main pathogens that cause infectious complications in OPFs [14]. Salášek et al, who reported on surgical site infections in patients with pelvic ring injuries, found that coagulase-negative Staphylococcus, E. faecalis, Pseudomonas aeruginosa, and E. coli were the major pathogens [19]. In this study, the frequency of identi cation of major wound pathogens of pelvic infection was in the following order: E. faecalis, coagulase-negative Staphylococcus, E. coli, and S. aureus.…”
Section: Analysis Of Complication and Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsugawa et al reported that E. coli and Bacteroides are the main pathogens that cause infectious complications in OPFs [14]. Salášek et al, who reported on surgical site infections in patients with pelvic ring injuries, found that coagulase-negative Staphylococcus, E. faecalis, Pseudomonas aeruginosa, and E. coli were the major pathogens [19]. In this study, the frequency of identi cation of major wound pathogens of pelvic infection was in the following order: E. faecalis, coagulase-negative Staphylococcus, E. coli, and S. aureus.…”
Section: Analysis Of Complication and Clinical Outcomesmentioning
confidence: 99%
“…Several researchers have reported that the presence of shock, advanced sepsis, intra-abdominal injury, and low Glasgow coma scale are risk factors for the occurrence and death from pelvic infections in OPFs [2,7,8,12]. Early faecal diversion, repeated irrigation and debridement, negative pressure wound therapy, external xation of the pelvis, and early multidisciplinary approaches have been reported as methods for treating pelvic infections caused by OPFs [6,8,10,11,[13][14][15][16][17][18][19]. Despite the development of these treatment strategies, OPFs are associated with high incidence of complications, long treatment periods, increased utilisation of medical resources, and high medical costs [3,5,8,10,11].…”
Section: Introductionmentioning
confidence: 99%